2008
DOI: 10.1038/cdd.2008.124
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an antiapoptotic protein complex at death receptors

Abstract: Stimulation of death receptors activates the extrinsic apoptotic signaling pathway that leads to cell death. Although many steps of this apoptotic signaling cascade are known, few mechanisms that counterbalance the death signal have been described. We identified an antiapoptotic protein complex associated with death receptors that contains glycogen synthase kinase-3 (GSK3), DDX3 and cellular inhibitor of apoptosis protein-1 (cIAP-1). GSK3, DDX3 and cIAP-1 are associated in cells with each other and with death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
99
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 39 publications
8
99
0
Order By: Relevance
“…29 In that study, Gsk3b inhibited apoptosis by interfering with DISC formation and caspase-8 activation. Our data reveal other possible mechanisms through which Gsk3 might inhibit apoptosis, that is, through regulation of p27 expression and that of downstream caspase-3 ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In that study, Gsk3b inhibited apoptosis by interfering with DISC formation and caspase-8 activation. Our data reveal other possible mechanisms through which Gsk3 might inhibit apoptosis, that is, through regulation of p27 expression and that of downstream caspase-3 ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…19 Several studies indicated that inhibition of Gsk3b activity in cancer cells potentates apoptosis stimulated by death receptor. [29][30][31][32] Furthermore, knocking out Gsk3b or inhibiting Gsk3b using lithium chloride, potentates TNF-induced apoptosis, indicating an anti-apoptotic role for Gsk3b. 30 Therefore, we asked whether c-FLIP L -mediated reduction of Gsk3b phosphorylation, and thus increase in its kinase activity, might be necessary for the anti-apoptotic function of c-FLIP L .…”
Section: Discussionmentioning
confidence: 99%
“…This pathway induces both CAM-DR of leukemic cells in response to daunorubicin and resistance to tumor necrosis factor-a. GSK3b-dependent cell survival implicates nuclear factor-kB activation (Ougolkov et al, 2007) and negative regulation of both intrinsic and extrinsic caspase-dependent pro-apoptotic pathways (Sun et al, 2008). The GSK3b activation in adherent leukemic cells requires its serine 9 (ser-9) dephosphorylation by PP2A in an a 5 b 1 -associated signaling complex including active GSK3b, PP2A and the adaptor RACK1 (De Toni-Costes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, elevated expression of DDX3 was found in a highly aggressive metastatic breast cancer cell line, MDA-MB-231, as compared with non-metastatic MCF-7 cells, which show its potential role in aggressive breast cancers and associated metastasis. 5,6 We have previously reported that overexpression of DDX3 in immortalized non-turmorigenic MCF10A cells promoted neoplastic transformation as indicated by down regulation of a cell adhesion molecule, E-cadherin. 5 Down-regulation of E-cadherin is a common feature of a variety of metastatic epithelial tumors, including those of the lung, breast and prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, elevated expression of DDX3 was found in a highly aggressive metastatic breast cancer cell line, MDA-MB-231, as compared with non-metastatic MCF-7 cells, which show its potential role in aggressive breast cancers and associated metastasis. 5,6 We have previously reported that overexpression of DDX3 in immortalized non-turmorigenic MCF10A cells promoted neoplastic transformation as indicated by down regulation of a cell adhesion molecule, E-cadherin.5 Down-regulation of E-cadherin is a common feature of a variety of metastatic epithelial tumors, including those of the lung, breast and prostate cancer.5,7-9 Hypoxic regions of solid tumors were considered to be the primary sites for the generation of the metastatic phenotype and have been demonstrated to be chemo and radio-resistant. [10][11][12][13][14] We have also reported that hypoxia inducible factor (HIF-1) induce the expression of DDX3 in two different breast cell lines by binding directly or indirectly to the hypoxia-response element (HRE) in the DDX3 proximal promoter.…”
mentioning
confidence: 99%